Hybrider le climat et les luttes - Berthier, Aurélien; Mourin, Barbara (Agir par la culture, 2018)
Le concept d’intersectionnalité définit les points de rencontre entre des luttes contre les dominations liées à la classe sociale, à la racisation ou au genre. Il a permis réflexions et nouveaux champs de bataille féconds. Activistes et intellectuel·les proposent de continuer à multiplier les hybridations entre ces combats sociaux, culturels et politiques avec les luttes environnementales et climatiques. Prenant... View Article
Keywords: approches et analyses; capitalisme; environnement; intersectionnalité; justice sociale; militance; patriarcat; projet charge mentale; ressource en ligne; systèmes d'oppressions; thématiques; écoféminisme

The Black feminist spatial imagination and an intersectional environmental justice - Ducre, Kishi Animashaun (Environmental Sociology, 2018)
Starting with seminal work from Katherine McKittrick and Katherine McKittrick and the late Clyde Woods, this paper compares and contrasts articulations of justice as espoused by Black feminism, ecofeminism, and the movement for environmental justice. The utilization of an intersectional genealogical approach allows for examination of the ways in which these movements might serve as the ideological bases for a Black feminist spatial imagination and an intersectional environmental justice. A Black feminist spatial imagination is an orientation that accounts for the merger of frames around race, gender, and ecology; it serves as a unique departure from conventional Black feminist analysis by its particular attention to the construct of space in Black feminist epistemology. Analysis reveals that manifestos engage similar strategies around boundedness, an identification among a collective identity and the subject of reproductive justice and liberation as wresting control and self-determination of physical bodies. The final task is an outline of essential tenets for a singular notion of justice of a Black feminist spatial imagination which incorporates the spirit of all of three manifestos and expands current environmental justice discourse to include those ‘who know no one knows’ while highlighting Black women’s agency in environmentally degraded environments. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: afro-féminisme; amériques; approches et analyses; corps; environnement; féminismes noirs; intersectionnalité; justice environnementale; justice reproductive; projet charge mentale; régions géographiques; thématiques; écoféminisme; états-unis

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Section: 1 volume (unpaged) : chiefly illustrations (some color) ; 26 cm
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Glaciers, gender, and science: A feminist glaciology framework for global environmental change research - Carey, Mark; Jackson, M.; Antonello, Alessandro; Rushing, Jaclyn (Progress in Human Geography, 2016)
Glaciers are key icons of climate change and global environmental change. However, the relationships among gender, science, and glaciers – particularly related to epistemological questions about the production of glaciological knowledge – remain understudied. This paper thus proposes a feminist glaciology framework with four key components: 1) knowledge producers; (2) gendered science and knowledge; (3) systems of scientific domination; and (4) alternative representations of glaciers. Merging feminist postcolonial science studies and feminist political ecology, the feminist glaciology framework generates robust analysis of gender, power, and epistemologies in dynamic social-ecological systems, thereby leading to more just and equitable science and human-ice interactions.
Keywords: approches et analyses; discipline; environnement; glaciologie; histoire et politique; intersectionnalité; point de vue situé; projet charge mentale; sciences; sciences de la terre; thématiques; études postcoloniales

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences